2020
DOI: 10.26895/geosaberes.v11i0.1048
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of TBM Penetration Rate Using Support Vector Machine

Abstract: One of the most important issues in mechanized excavating is to predict the TBM penetration rate. Understanding the factors influencing the rate of penetration is important, which allows for a more accurate estimation of the stopping and excavating times and operating costs. In this study, Input and output parameters including Uniaxial Compressive Strength (UCS), Brazilian Tensile Strength (BTS), Peak Slope Index (PSI), Distance between Planes of Weakness (DPW), Alpha angle and Rate of Penetration (ROP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The correlation between predicted and actual TBM PR values for the ANN is plotted in Figure 15(b1,b2). In the past, ANN-based studies have shown R 2 values of 0.66 [8], 0.82 [62], 0.83 [63], 0.90 [53], and 0.94 [64]. Furthermore, the ANN algorithm has been used to perform different training functions (lbfgs, sgd, and ADAM) to predict the TBM performance, as shown in Figure 16.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between predicted and actual TBM PR values for the ANN is plotted in Figure 15(b1,b2). In the past, ANN-based studies have shown R 2 values of 0.66 [8], 0.82 [62], 0.83 [63], 0.90 [53], and 0.94 [64]. Furthermore, the ANN algorithm has been used to perform different training functions (lbfgs, sgd, and ADAM) to predict the TBM performance, as shown in Figure 16.…”
Section: Resultsmentioning
confidence: 99%
“…In a simple way, the support vectors are a set of points in ndimensional space of data which determine the border of classifications, so that the data classification could be carried out. The classification output can be changed as a result of moving one of the vectors [21]. The specification of SVM used in predicting penetration rate was listed in Table 2.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%